Total Saponins of Radix Clematis Regulate Fibroblast-Like Synoviocyte Proliferation in Rheumatoid Arthritis via the LncRNA OIP5-AS1/MiR-410-3p/Wnt7b Signaling Pathway. (27th May 2022) - Pan, Lingyu; Sun, Yuan; Jiang, Hui; Chen, Yan; Jiang, Yeke; Han, Yanquan; Wang, Yongzhong
Abstract : Background . Rheumatoid arthritis (RA) is the most common autoimmune disease and affects multiple joints. Previous studies have shown that total saponins of Radix clematidis (TSC) have a clear therapeutic effect on RA, but the specific mechanism has not yet been clarified. Literature screening and previous research suggest that the lncRNA OIP5-AS1/miR-410-3p/Wnt7b signaling pathway exerts a regulatory effect on the pathogenesis of RA. In this study, we examined whether the TSC treatment of RA affects the lncRNA OIP5-AS1/miR-410-3p/Wnt7b pathway. Materials and Methods . Freund's complete adjuvant was used to create an adjuvant arthritis (AA) rat model with rat synovial cells being harvested and cultured. The experiment comprises a normal group, model group, TSC optimal-dose group, TSC optimal-dose group + lncRNA OIP5-AS1siRNA group, lncRNA OIP5-AS1 siRNA group, and lncRNA OIP5-AS1 siRNA + NC group. MMT was used to screen the optimal concentration of TSC. The level of lncRNA OIP5-AS1, miR-410-3p, Wnt7b, β -catenin, c-Myc, cyclin D1, GSK-3 β, and SFRP4 mRNA were detected by real-time-qPCR, the expression of Wnt7b, β -catenin, c-Myc, cyclin D1, GSK-3 β, and p-GSK-3 β (Ser9) protein were detected by immunofluorescence and Western blot. Results . We found that TSC inhibits the proliferation of RA FLS, TSC significantly reduced lncRNA OIP5-AS1, Wnt7b, β -catenin, c-Myc, cyclin D1, and p-GSK-3 β /GSK-3 β mRNA/protein expression, whereas the miR-410-3p and SFRP4 mRNA/protein expression levels were significantly upregulated. Our data suggest that TSC can inhibit the excessive proliferation of FLS to treat RA, the mechanism of which may be closely related to regulation of the lncRNA OIP5-AS1/miR-410-3p /Wnt7b signaling axis and the Wnt signaling pathway.